Mixed mode I + II interlaminar fracture of glass/epoxy multidirectional laminates - Part 1: Analysis - Morais, A.B. de
An analytical study was conducted on mixed mode bending (MMB) glass/epoxy multidirectional specimens with delaminations in 0/theta and theta/-theta type interfaces. Three-dimensional finite element models and the virtual crack closure technique (VCCT) were used to evaluate a modified beam theory (MBT) data reduction scheme. The specimen compliance and total strain energy release rate G were accurately predicted by MBT, and there were only small mode partitioning differences relative to VCCT for 0/theta specimens. Moreover, VCCT mode partitioning for 0/45 and 0/90 specimens rapidly converged to MBT predictions for increasing crack closure increments of the order of the fracture process zone.